2019
DOI: 10.1159/000502491
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebellar Size at Term-Equivalent Age Is Related to a 17% Lower Mental Developmental Index in Very Preterm Infants without Brain Injury

Abstract: <b><i>Introduction:</i></b> Cerebellar injury is increasingly recognized as a relevant complication of premature birth. However, the prevalence of reduced cerebellar growth and its consequences for neurodevelopmental outcome in preterm infants without overt brain injury remain to be defined in detail. The aim of this study was to assess the transcerebellar diameter (TCD) at term-equivalent age (TEA) in very preterm infants without brain injury and to evaluate whether TCD is related to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Cognitive and motor functions are often compromised by brain injury, which affects 25% of all very preterm infants [2,3]. Nevertheless, some infants without brain in-DOI: 10.1159/000506836 jury such as intraventricular/cerebellar haemorrhage or periventricular white matter injury visible on conventional magnetic resonance imaging (MRI) at term-equivalent age (TEA) are also affected by adverse outcome [4]. Recently, we demonstrated that in infants without ostensible brain injury a reduced cerebellar size at TEA is related to a lower Mental Developmental Index (MDI) at 2 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive and motor functions are often compromised by brain injury, which affects 25% of all very preterm infants [2,3]. Nevertheless, some infants without brain in-DOI: 10.1159/000506836 jury such as intraventricular/cerebellar haemorrhage or periventricular white matter injury visible on conventional magnetic resonance imaging (MRI) at term-equivalent age (TEA) are also affected by adverse outcome [4]. Recently, we demonstrated that in infants without ostensible brain injury a reduced cerebellar size at TEA is related to a lower Mental Developmental Index (MDI) at 2 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some infants without brain in-DOI: 10.1159/000506836 jury such as intraventricular/cerebellar haemorrhage or periventricular white matter injury visible on conventional magnetic resonance imaging (MRI) at term-equivalent age (TEA) are also affected by adverse outcome [4]. Recently, we demonstrated that in infants without ostensible brain injury a reduced cerebellar size at TEA is related to a lower Mental Developmental Index (MDI) at 2 years of age [4]. Conversely, we found no significant relationship between cerebellar size and Psychomotor Developmental Index (PDI), and there are still infants at risk for adverse outcome who go undetected [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, previous findings demonstrate that cerebellar injury plays an important role in the high prevalence of nonmotor deficits (ie, cognition, learning, and behavior) in survivors of prematurity. 3,4 During the third trimester of pregnancy, the cerebellum exhibits a rapid increase in growth and development. 2 Any disturbance of cerebellar growth, for example, by hypoxia-ischemia or inflammation, may lead to irreversible aberrations of the cerebellar integrity.…”
Section: Introductionmentioning
confidence: 99%
“…HIE was recognized primarily as a white matter disease of the cerebrum, leaving cerebellar involvement underappreciated in the clinical setting 2 . However, previous findings demonstrate that cerebellar injury plays an important role in the high prevalence of nonmotor deficits (ie, cognition, learning, and behavior) in survivors of prematurity 3,4 …”
Section: Introductionmentioning
confidence: 99%